EVALUASI PENGELOLAAN BANK SAMPAH DI KOTA MOJOKERTO - Umrotul Malikah; Darjati .; Demes Nurmayanti (Poltekkes Kemenkes Surabaya, 2021)
Waste management is one of the problems that needs to be prioritized in preserving the urban environment. The Randegan Final Disposal Site in Mojokerto City is unable to accommodate the volume of waste, one of the programs by carrying out Waste Bank activities based on Law Number 18 of 2008 concerning Waste Management. The purpose of this study is to evaluate the planning, organization, implementation, and supervision of waste bank management in Mojokerto City.This study uses a qualitative descriptive approach with interview techniques, field observations and Document Search. The data are grouped based on internal and external environmental factors that exist in the waste banks in 3 (three) sub-districts of Mojokerto City, totaling 25 waste banks. The data obtained were analyzed using SWOT. The results showed that the Strength factor was 1.316 Weakness was 1.361. Opportunity 1.730440232. and Treat 1.147155115. The difference in the total score of the Strenght and Weakness factors (-) is 0.045. The difference in the total score of the Opportunity and Treath factors (+) is 0.583. Position in Quadrant III means that the organization is in a weak position but has a lot of opportunity. The strategy that must be applied in the management of waste banks in Mojokerto City is the WO (Weakness-Opportunity) Strategy, is a combination of internal weakness factors with external opportunity factors.